Molecular Epidemiology of Cryptosporidiosis on Lamb and Goat Kid Farms in Gran Canaria, Canary Islands (Spain) - María Cristina Del Río; Sergio Martín; Joaquín Quílez; José Manuel Molina; Otilia Ferrer; José Adrián Molina; Adrián Melián; Antonio Ruiz (Microorganisms)
The aim of this study was to analyse and characterise Cryptosporidium spp. in sheep and goats in Gran Canaria (Spain) and to identify the risks and economic factors related to the disease. During sampling, a semi-structured survey was conducted with farmers, and faecal samples were collected from lambs, goat kids, sheep, and adult goats from a total of 30 farms. Adult samples were examined microscopically for the presence of Cryptosporidium spp. oocysts, with only three positive samples being found in sheep and one in goats. The PCR of the SSU rRNA gene was performed on all juvenile and adult samples, and positive samples from lambs (8.3%), sheep (6.9%), goat kids (23.3%), and goats (2.5%) were subjected to sequencing, detecting three of the most important species in small ruminants: C. parvum, C. xiaoi, and C. ubiquitum. By sequencing the GP60 PCR products, two subtypes of C. parvum belonging to the IId family were identified, IIdA16G1 and IIdA23G1, with the latter being the most frequent. Although the prevalence of the disease was not very high, the zoonotic potential of C. parvum and the limited awareness of the parasite among farmers make surveillance and health education focused on the control of this member of Apicomplexa necessary.